1999
DOI: 10.1093/alcalc/34.3.386
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Preference for Sweets and Excessive Alcohol Intake: A Review of Animal and Human Studies

Abstract: This report reviews a series of studies demonstrating a relationship between the consumption of sweets and alcohol consumption. There is consistent evidence linking the consumption of sweets to alcohol intake in both animals and humans, and there are indications that this relationship may be at least partially genetic in nature. Alcohol-preferring rats have a tendency to consume sucrose and saccharin solutions far beyond the limits of their normal fluid intake and this has been proposed to be a model of the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
97
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(111 citation statements)
references
References 71 publications
11
97
0
3
Order By: Relevance
“…It is also curious that for PTC, the non-taster allele is associated with higher alcohol intake (among people who are not problem drinkers) but the non-taster allele is associated with lower sweet preference, at least in children. This observation is inconsistent with the greater sweet preference in alcoholics [51]. Taste could be a more important regulator of alcohol consumption than previously appreciated [107], but the interactions among sweet liking, alcohol consumption and taste will no doubt be more complex than a simple one-to-one correspondence between genotype and behavior.…”
Section: Genotype-phenotype Studiesmentioning
confidence: 74%
See 2 more Smart Citations
“…It is also curious that for PTC, the non-taster allele is associated with higher alcohol intake (among people who are not problem drinkers) but the non-taster allele is associated with lower sweet preference, at least in children. This observation is inconsistent with the greater sweet preference in alcoholics [51]. Taste could be a more important regulator of alcohol consumption than previously appreciated [107], but the interactions among sweet liking, alcohol consumption and taste will no doubt be more complex than a simple one-to-one correspondence between genotype and behavior.…”
Section: Genotype-phenotype Studiesmentioning
confidence: 74%
“…Family studies of addiction have demonstrated that alcoholics and their family members prefer sweeter solutions than do nonalcoholic family members, suggesting that alcohol and sweeteners may share similar brain reward pathways [51]. The hypothesis that the rewarding properties of opioid-receptor-stimulating drugs and sweet taste are controlled by a common neural substrate is upheld further by the ability of naloxone, an opioid antagonist, to reduce both the positive properties of opiates and the preference for the taste of sweet [52,53].…”
Section: Nerves and Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…[36][37][38][39] In humans, opiate-dependent subjects on methadone maintenance report higher consumption of sweets than control subjects, 40 and subjects diagnosed with alcohol dependence or cocaine abuse/dependence tend to prefer sweeter sucrose solutions than controls. 41,42 After reviewing the similarities between the effects of sugar ingestion and those related to drug addiction, Avena et al 43 conclude that under some circumstances, sugar can be addictive. Among the behavioral evidence supporting this view is the observation of signs of opioid withdrawal after naloxone is given to the rats maintained on a cyclic regimen of access to a glucose solution.…”
Section: Interactions Between Palatability and Drugs Of Abusementioning
confidence: 99%
“…A number of researchers have suggested that increased sweet taste response is significantly and positively related to increased risk of extreme alcohol consumption and it has been proposed that the brain reward system may be implicated (Kampov-Polevoy, Eick, Boland, Khalitov, & Crews, 2004;Kampov-Polevoy, Garbutt, & Janowsky, 1999;Lange, Kampov-Polevoy, & Garbutt, 2010). In a previous study, Ghemulet, Baskini, Messinis, Mouza, and Proios (2014) explored any possible relationship between verbal fluency production using verbal fluency tasks (VFT) and a card sorting task in the principal taste domains (i.e.…”
Section: Psychological Thought Psyctpsychopeneu | 2193-7281mentioning
confidence: 99%